LEGAL ISSUES OF DIGITAL TRANSFORMATION IN THE FIELD OF PHYTOSANITARY SAFETY (Journal of actual problems of jurisprudence, 2025)
In the context of rapid development and integration of digital technologies into key sectors of social and economic life, the Republic of Kazakhstan faces the challenge of revising its approaches to the legal provision of phytosanitary security. This study aims to develop scientifically grounded legal solutions that take into account the specifics of digital transformation and focus on updating the current legislation.The analysis of the existing legal framework revealed inconsistencies and legislative gaps that hinder the full implementation of digital tools in the field of phytosanitary safety. Significant emphasis was placed on studying international experience, as well as assessing the potential for Kazakhstan’s integration into the international system of electronic phytosanitary certificates, IPPC e-Phyto, which is an important step toward the international recognition of digital documents and the simplification of procedures in foreign trade.The methodological framework of the study is based on comparative legal analysis, legal modeling, and forecasting of regulatory risks. As a result of the research, a number of practical proposals have been formulated aimed at eliminating identified barriers, including the normative consolidation of the use of electronic certificates, ensuring legal protection of personal data, expanding digital infrastructure in agricultural regions, and increasing the level of digital competence among representatives of the agricultural sector. The findings of this study may serve as a foundation for the development of a national strategy for the digital transformation of legal regulation in Kazakhstan’s agricultural sector.Keywords: digital transformation, phytosanitary security, legal regulation, electronic phytosanitary certificates, digital infrastructure, data protection, digital literacy.